LANGUAGE INTERVENTION FOR A YOUNG LEARNER UNDERGOING BILINGUAL DEVELOPMENT PROBLEMS AS SYMPTOMS OF AUTISTIC SPECTRUM DISORDER - Fitri Darsini (ICoTE Proceedings)
Despite all benefits of bilingualism, young children who are exposed to dual language through early media viewing may experience language development problems. It may consequently lead them to undergo therapies which can be counterproductive to their developmental milestones, especially to their dual language development.  This research aims to gain deeper insights about the impact of early media viewing on a young child’s early dual language acquisition and how language intervention in an inclusive setting of education conducted in ZonaKata School of Language improve his dual language development.  A case study of a young dual language learner experiencing language development problems diagnosed as symptoms of Autistic Spectrum Disorder (ASD) was conducted by interviewing participant’s parents to gain preliminary data about his language development problems.  Observations took place during 108-hour language intervention sessions.  The finding is that early dual language exposure through early media viewing without adequate social interaction pertinently results in language development problems which are prone to be interpreted as symptoms of ASD rather than as a natural process of bilingualism. Language intervention conducted in an inclusive setting of education which stimulates social interaction and communication can productively support a young learner’s dual language development.